Pseudomonas Aeruginosa Continues its March on the Road of Antibiotic Resistance in Pakistan - Naeem, Afnan; Usman, Javaid; Furqan, Warda; Waseem, Hafsa; Tayyab, Nadia; Hanif, Faisal (International Journal of Pathology, 2023)
Objective: The main aim of study was to find the frequency and to determine the current susceptibility pattern of multi-drug resistant (MDR), extensively drug resistant (XDR) and pan drug resistant (PDR of Pseudomonas aeruginosa isolated from different clinical specimens.Material and Methods: It was a cross-sectional single center study. This study was carried out at Microbiology department of Army Medical College (National University of Medical Sciences)/Pak Emirates Military Hospital (PEMH) Rawalpindi, Pakistan from March 2019 to Aug 2019 after obtaining permission from ethical review board of institute.All clinical samples received in microbiology laboratory for culture and sensitivity of Pseudomonas aeruginosa were included except for urinary catheter and endotracheal tips. Exclusion criteria consisted of duplicate samples of same patient. Specimens were inoculated on different culture media like Blood agar, MacConkey agar depending on requirement of specimen. Gram stain, colony morphology was done initially and standard microbiological methods like oxidase test, catalase test and Analytical profile index (api-20 NE) biomerieux was used for identification of isolates. Isolates were identified till species level. Kirby-Bauer modified disc diffusion method was used to find the antibiotic susceptibility and results were interpreted using the Clinical and Laboratory Standards Institute (CLSI) guidelines.Results: During the study period, 157 Pseudomonas aeruginosa were detected from different clinical specimens. Multi drug resistant Pseudomonas aeruginosa was detected in 37 (23.6%) isolates. Frequency of extensively drug resistant Pseudomonas aeruginosa was found to be 20 (12.7 %). Pan drug resistance was seen in 4 (2.5%) percent isolates of Pseudomonas aeruginosa. Colistin was found to be most sensitive drug i.e. (75.6%) in multi drug resistant and (90%) in extensively drug resistant isolates of Pseudomonas aeruginosa. After Colistin in multidrug resistant strains Piperacillin-Tazobactam (75.6%) and Meropenem (62.1%) were sensitive whereas extensively drug resistant strains were most susceptible to Colistin (90%) and Aztreonam (15%).Conclusion: Multi drug resitant infections are on rise. Pseudomonas aeruginosa infections that are multi drug resistant and extensively drug resistant are occurring at a significant rate and are leading towards era of ineffective and limited therapeutic options which can be avoided by adopting antibiotic stewardship and creating more awareness about antibiotic resistance and adhering to local antibiogram.